City Leadership for Health and Well-being: Back to the Future - Tsouros, Agis (Springer US, 2013)
The new European Health Policy Framework and Strategy: Health 2020 of the World Health Organization, draws upon the experience and insights of five phases, spanning 25 years, of the WHO European Healthy Cities Network (WHO-EHCN). Applying the 2020 health lens to Healthy Cities, equity in health and human-centered sustainable development are core values and cities have a profound influence on the wider determinants of health in the European population. “Making it Happen” relies on four action elements applied and tested by municipalities and their formal and informal partners: political commitment, vision and strategy, institutional change, and networking. In turn, the renewed commitment by member states of the WHO Regional Committee to work with all spheres and tiers of government is a new dawn for city governance, encouraging cities to redouble their investment in health and health equity in all policies, even in a period of austerity. For phase VI, the WHO-EHCN is being positioned as a strategic vehicle for implementing Health 2020 at the local level. Healthy Cities' leadership is more relevant than ever.